KEBERADAAN MINI MARKET DI NAGARI IV KOTO PULAU PUNJUNG KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA - Vilia, Gita - (STKIP PGRI Sumbar, 2014)
This study aims to gain an overview of the existence of a mini market, in terms of: 1) a small stall trader, 2) employment, 3) consumption.The research is a qualitative, the subject of this research through a snow ball, the data collected through; 1) observation, 2) interviews, 3) documentation. Informants in this study is a small stall trader, owner of a mini market and public spending in the mini market were 17. Testing the validity of the data in the study used data analysis techniques, the validity of the data, and triangulation.The results showed that: the existence of a mini market in the Nagari IV Koto Pulau Punjung Kecamatan Pulau Punjung Kabupaten Dharmasraya is 1) a decrease in consumer spending to a traders stall resulting in loss of income suffered by a small stall trader Nagari IV Koto Pulau Punjung. 2) since the presence of a mini market in the Nagari IV Koto Pulau Punjung can create jobs so as to increase the income for workers. 3) consumption spending most of todays society there are not affected in spending and there is also a change in spending that result from the presence of a mini market in the Nagari IV Koto Pulau Punjung. Judging from the presence of the mini market in the Nagari IV Koto Pulau Punjung Kecamatan Pulau Punjung Kabupaten Dharmasraya that the public expects that the existence of a mini market can help the public to boost employment.